Herschel-ATLAS : the spatial clustering of low- and high-redshift submillimetre galaxies. Issue 4 (10th November 2018) - Amvrosiadis, A; Valiante, E; Gonzalez-Nuevo, J; Maddox, S J; Negrello, M; Eales, S A; Dunne, L; Wang, L; van Kampen, E; De Zotti, G; Smith, M W L; Andreani, P; et al.
Abstract: We present measurements of the angular correlation function of sub-millimetre (sub-mm) galaxies (SMGs) identified in four out of the five fields of the Herschel Astrophysical Terahertz Large Area Survey (H-ATLAS) – GAMA-9h, GAMA-12h, GAMA-15h, and NGP – with flux densities$S_{250 \, μ {\rm m}} \gt 30$ mJy at 250 μm. We show that galaxies selected at this wavelength trace the underlying matter distribution differently at low and high redshifts. We study the evolution of the clustering finding that at low redshifts sub-mm galaxies exhibit clustering strengths of r 0 ∼ 2–3 h −1 Mpc, below$z$ < 0.3. At high redshifts, on the other hand, we find that sub-mm galaxies are more strongly clustered with correlation lengths r 0 = 8.1 ± 0.5, 8.8 ± 0.8, and 13.9 ± 3.9 h −1 Mpc at$z$ = 1–2, 2–3. and 3–5, respectively. We show that sub-mm galaxies across the redshift range 1 <$z$ < 5, typically reside in dark-matter halos of mass of the order of${\sim } 10^{12.5}\hbox{--}10^{13.0} \, h^{-1}\, M_{\odot}$ and are consistent with being the progenitors of local massive elliptical galaxies that we see in the local Universe.